A competitive nature-derived multilayered scaffold based on chitosan and alginate, for full-thickness wound healing. (15th June 2021) - Vakilian, Saeid; Jamshidi-adegani, Fatemeh; Al Yahmadi, Afra; Al-Broumi, Mohammed; Ur Rehman, Najeeb; Anwar, Muhammad U.; Alam, Khurshid; Al-Wahaibi, Nasar; Shalaby, Asem; Alyaqoobi, Sausan; Al-Harrasi, Ahmed; Mustafa, Kamal; et al.
Graphical abstract: Highlights: A three-layered scaffold based on Chitosan and Alginate, were developed. DC and AV were characterized and loaded as separate layers. The scaffold represented adequate porosity, water uptake and degradation properties. The in vitro results revealed the excellent biocompatibility of the scaffold. The in vivo performance of the scaffold promoted the tissue regeneration. Abstract: The aim of this study was to evaluate a bioactive multilayer wound dressing, based on chitosan and alginate. To enhance healing potential, Dracaena Cinnabari and Aloe Vera were loaded as separate layers into the scaffold. The bare and bioactive multilayered scaffolds were fabricated by an iterative layering freeze-drying technique. Following of topographical, chemical, and physical assessment, the performance of the scaffolds was evaluated in vitro and in vivo . The results revealed adequate attachment, and proliferation of human foreskin fibroblasts, indicating excellent biocompatibility of the bioactive scaffold. In vivo, the performance of the multi-layered scaffold loaded with the bioactive materials was comparable with Comfeel plus®. The wounds treated with the bioactive scaffold exhibited superior hypergranulation, fibroblast maturation, epithelization, and collagen deposition, with minimal inflammation, and crust formation. It is concluded that the synergism of extracellular matrix-mimicking multi-layered scaffolding with Aloe Vera and Dracaena Cinnabari could be considered as a supportive wound dressing.